Digital Heritage: A legal study compared to Islamic jurisprudence - الشمري, حيدر حسين; الخزاعي, صفاء متعب (Journal of Legal Sciences, 2020)
The idea of ​​digital legacy is a very modern issue in the legal reality, as it did not appear until this decade, and the signs of its emergence in America are originating from Iraq by an American soldier who was killed in Iraq. The legal position of the accounts and pages and the content of the accounts and personal pages left by the human being after his death, and can it be passed on after him to the heirs or not? It is the general successor who deserves this digital stuff.         When reviewing the position of comparative laws of American, English, French, Iraqi and Islamic jurisprudence, we find that the essence of the problem raised by the issue of digital heritage is the collision of the privacy of the deceased. Conflict between the transmission of digital heritage on the one hand and the right of privacy of the deceased on the other.